Jurnalisme Warga Sebagai Alternatif Literasi Media dan Partisipasi Bagi Publik - Alwaton, Yogie (Avant Garde, 2023)
This research aims to provide a mapping and elaborative explanation regarding the form of citizen journalism in Indonesia as an alternative means of media literacy and participation for the public. Apart from that, this research is also aimed at reviewing whether professional journalists and citizen journalists can collaborate due to the lack of perception that citizen journalism threatens the profession of professional journalism, and the final question will focus on the challenges of citizen journalism in ethical issues. To answer this problem, researcher used a literature study method by observing 31 relevant scientific journal articles, books and internet sources. The results of this research reveal that citizen journalism was born as a counter discourse to the practice of professional journalism which is full of interests and often neglects the public interest. The implication that emerges is that there is a form of citizen journalism in Indonesia which is an alternative for ordinary citizens to participate in a broad agenda and the growth of media literacy space for citizens. Forms of citizen journalism in Indonesia can be found in various forms of citizen journalism in Indonesia such as mainstream television media, online mainstream media, and citizen journalism in alternative media. Citizen journalism in Indonesia can also collaborate with each other and will not replace the profession of professional journalism. Finally, regarding the credibility of the issue, citizen journalists are very vulnerable to being exposed to legal regulations. However, this can be hit by various opportunities to provide them with training so that the quality of information and news is beyond doubt.